Diagnosis of imported malaria in Japan by using microtiter plate-hybridization technique - Akter, Tangin (Bangladesh Journal of Zoology, 2015)
In Japan, malaria has been successfully eradicated but imported malaria is still a great problem. Blood samples of malaria patients were collected from different hospitals of Japan. The samples were diagnosed by PCR based Microtiter plate-hybridization technique (MPH). The results of MPH were compared with microscopic diagnosis done at the laboratories of different hospitals. Among the total 23 blood samples examined, 19 were diagnosed as malaria parasite positive by MPH technique. The malaria parasites found were Plasmodium falciparum 7 (36.7%), Plasmodium vivax 6 (31.6%), Plasmodium ovale 1 (5.3%), Plasmodium ovale variant 3 (15.8%), Plasmodium malariae 1 (5.3%). One mixed infection of P. falciparum and P. ovale (5.3%) were also recorded. The area of acquisition of malaria was highest from Africa followed by Oceania, Asia, South America and others. This investigation indicated the MPH technique was more specific than microscopy for the diagnosis of imported malaria. Bangladesh J. Zool. 41(2): 241-246, 2013